LDL TEROKSIDASI DAN KEPADATAN MINERAL TULANG (Oxidized LDL Cholesterol and Bone Mineral Density) - Sheila Febriana; Yurdiansyah Yurdiansyah; Siti Rafiah; Ruland DN Pakasi; Uleng Bahrun (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Osteoporosis is defined by low bone density and micro architectural deterioration of bone tissue with a consequent increase in bonefragility and risk of fracture. Bone Mineral Density (BMD) is a gold standard for the diagnosis of osteoporosis, which need special device,and expensive fee. So it is not routinely done, therefore another type of examination methods is needed. Oxidized LDL (oxLDL) cholesterolis the parameter correlated with diminished bone mineral density by affecting osteoblast and osteoclast. The aim of this study was toknow the role of oxLDL in diminished bone mineral density by analyzing it. Cross sectional study was held on 78 subjects during theperiod of October 2011 until June 2013 using the primary data from 30−60 years women population in Makassar, whose FPG, ALT,AST, urea and creatinine are within normal limit. Using oxLDL 6.8mU/L value as cut off, had found odds ratio increase 2.2 times with68.8% probability to suffer diminished BMD. Receiver Operating Characteristic (ROC) analysis show area under curve is 60.8%, using8.05mU/L as a cut off point resulting 68.8% sensitivity, 59.2% specifity, 76.1% positive predictive value, 50% negative predictive value,1.71 positive likelihood ratio, 0.53 negative likelihood ratio and 65.4% accuracy. Concluded that oxLDL ≥6.8mU/L increases risk tosuffer diminished BMD 2.2 times. As a diagnostic marker, oxLDL has a weak diagnostic strength and accuracy (68.8% sensitivity and59.2% specifity). The researchers have the opinion to perform a further study with larger and various population, concern on oxLDLbio availability and use it with another parameter as a panel test.